Perfectionistic self-presentation moderating effect of responsibility beliefs on help-seeking intention - Lee, Yi Fan (Nanyang Technological University, 2024)
Stigma is a barrier to help-seeking for mental illnesses. Stigmatization of the depressives stems from the belief that the depressives are responsible for their mental illness. The current study examined whether altering responsibility beliefs would alleviate stigmatization of the depressives, thereby improving people’s intention to seek help for depression. The study also assessed whether individuals highly concerned with projecting a social image of perfection (i.e., perfectionistic self-presentation) would have weaker help-seeking intention than individuals without such concerns. The potential role of perfectionistic self-presentation in moderating the relationship between responsibility beliefs and help-seeking intention was also assessed. 45 Singapore residents were each presented with a vignette which served to manipulate their responsibility beliefs. They then reported their intention to seek help if they were depressed. They also rated the extent of their concerns with perfectionistic self- presentation. The results showed that responsibility beliefs did not have a significant main effect on help-seeking intention. Out of the three perfectionistic self-presentation facets, only non-disclosure of imperfection had a significant main effect on intention to seek formal help for depression. All three perfectionistic self-presentation facets did not have a significant main effect on intention to seek informal help for depression. Perfectionistic self-presentation did not moderate the relationship between responsibility beliefs and help-seeking intention. Overall, our findings suggest that altering responsibility beliefs might not be effective in improving intention to seek help for depression, and that interventions targeting factors other than responsibility beliefs might be necessary. Implications of the findings will be further discussed.